The Cult of the Market Economic Fundamentalism and its Discontents - Boldeman, Lee (ANU Press, 2007)
The Cult of the Market: Economic Fundamentalism and its Discontents disputes the practical value of the shallow, all-encompassing, dogmatic, economic fundamentalism espoused by policy elites in recent public policy debates, along with their gross simplifications and sacred rules. Economics cannot provide a convincing overarching theory of government action or of social action more generally. Furthermore, mainstream economics fails to get to grips with the economic system as it actually operates. It advocates a more overtly experimental, eclectic and pragmatic approach to policy development which takes more seriously the complex, interdependent, evolving nature of society and the economy. Importantly, it is an outlook that recognises the pervasive influence of asymmetries of wealth, power and information on bargaining power and prospects throughout society. The book advocates a major reform of the teaching of economics.